Development Beyond Neoliberalism? Governance, poverty reduction and political economy - David Craig, Doug Porter (Routledge, 2006)
Development’s current focus – poverty reduction and good governance – signals a turn away from the older neoliberal preoccupation with structural adjustment, privatization, and downsizing the state. For some, the new emphases on empowering and securing the poor through basic service delivery, local partnership, decentralization and institution building constitute a decisive break with the past, and a whole set of new Development possibilities beyond neoliberalism. Taking a wider historical perspective, this book charts the emergence of poverty reduction and governance at the centre of Development. It shows that the Poverty Reduction paradigm does indeed mark a shift in the wider liberal project that has underpinned Development: precisely what is new and what this means for the ways the poorer parts of the planet are governed are here described in detail. This book provides a compelling history of Development doctrine and practice, and in particular offers the first comprehensive account of the last 20 years, and Development’s shift towards institution building, decentralized governance and local partnerships. The story is illustrated with extensive case studies from first-hand experience in Vietnam, Uganda, Pakistan and New Zealand.